Spatial Interdependence of Brazilian Exports: Impacts on Regional Labor Markets - Jose Paulo Chahad; Antonio Evaldo Comune; Eduardo Haddad (European Regional Science Association (ERSA), 2004)
This paper analyzes the interdependence among Brazilian states associated with employment generation by the export sector. Using a unique database — an interstate input-output table for 1996 — employment multipliers are calculated for six different skill groups. Multiplier decomposition techniques are also used in order to reveal intrastate and interstate patterns of dependence. The analysis of the regional impacts of state exports on employment suggests a concentration of skilled labor content in the states in the Southeastern and Southern regions. More developed states benefit to a great extent from Brazilian exports, responding directly and indirectly to the demand for skilled workers.
Keywords: 330